Observations de Geomorphologie Littorale a Mamba Point (Monrovia, Libéria) - Tricart, Jean (ERDKUNDE, 1962)
Cape Mamba Point is formed as a working cliff as a result of the very slow weathering of the dolerite and shows the exact arrangement of the shoreline-forming processes in well-differentiated elevations. The salty spray prevents the emergence of vegetation on the top of the cliff. The following processes interact: Pockmarked salt weathering, sometimes leading to the formation of small holes; thermal microdesquamation; decomposition by lower plants, but limited to a transition zone on the summit. Further below, where the rocks are washed by the sea or temporarily submerged at the time of high tide, is the area of corrosion with barrows and grooving. Still deeper, in the lower part of the intertidal area, a thin layer of algae covers a sharp-edged micro relief. The working is very weak. All these processes create exclusively sandy grus. It is carried away by the waves together with the blocks detached from the association by fissure weathering at the level of the high tide line and immediately below it. The waves thunder against the blocks until they fall or slide below the tidal range. Here they are no longer moved and gradually become covered with algae. The interaction of these processes explains that along such coasts only sand and large blocks (1 m and more) occur, without the intermediate fractions typical of cliffs in the humid tropical zone. Among tropical coasts, Mamba Point represents a transitional type, similar to that in some parts of eastern Brazil (e.g., Salvador area). The humid air and the absence of distinctly dry seasons prevent the formation of holes by salt blasting; the excessive frequency of fissures also has an inhibiting effect in this respect. The salt effect is most intense where the climate is drier (Dakar area), Cabo Frio in Brazil), conversely it recedes more strongly in the Ivory Coast, where evaporation is even lower. Thus, in the tropics, depending on the prevailing climate, there are different climamorphological cliff coast types. They can be used for the reconstruction of recent paleoclimates, as author has done on the example of Brazil. On the other hand, in the Monrovia area, the level of maximum morphogenetic effectiveness, where beach terraces are formed, is about the same as the sea level. In temperate latitudes it is lower, about the level of the tidal range. Where salt crystallization is more intense, the level is even higher, above the highest water level. It is necessary to take this fact into account in explaining and correlating recent sea level levels. It helps us to explain the different elevations of certain postglacial beach terraces of tropical latitudes, and likewise the different elevations of tropical and extratropical terraces.